Intellectual Migration of the Frankfurt School to America and the Rise of New Social Movements (1930-1960) - Dharyanto Tito Wardani; Alija Izetbegovic (Jurnal Artefak, 2025)
This study examines the impact of the National Socialist regime’s rise to power on the community of social science scholars at the University of Frankfurt and its broader implications for the development of modern social thought. The increasing dominance of anti-Semitic and racial ideology in pre-World War II Germany forced many Frankfurt intellectuals to flee for safety, leading to the dispersion of key scholars to various countries, including the United States. The research aims to explain how this displacement contributed to an epistemological shift from the Frankfurt School to the Chicago School, which later influenced the emergence of contemporary New Social Movements. Employing historical methods consisting of heuristics, source criticism, interpretation, and historiographical synthesis, the study analyzes the intellectual networks of scholars in Germany and the United States, the trajectory of the Institute for Social Research, and its relocation from Frankfurt to Chicago. The findings show that the transformation of German critical theory in the United States produced new frameworks that combined postmodern and Marxian perspectives, shaping movements such as anti-war activism, Black civil rights, feminism, and environmentalism. The study contributes to historical scholarship by highlighting how intellectual migration reshaped critical theory and laid the groundwork for modern sociopolitical movements.